1999
DOI: 10.1111/j.1751-1097.1999.tb08296.x
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry and Photophysics of Papaverine N‐Oxide

Abstract: The photochemistry and photophysics of papaverine N‐oxide in polar aprotic and protic solvents has been studied in detail. Complex energy and charge‐transfer phenomena between chromophores occur in papaverine. New photochemistry for the papaverine N‐oxide system is reported. Irradiation in protic media results in the formation of an emissive charge‐transfer state with ensuing intramolecular hydroxylation in high isolated yields (75–80%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The photoinduced deoxygenation of N-oxides has been reported previously for other molecules (10) and was found to proceed on irradiation of N-oxide alone or in the presence of suitable acceptors such as amines (11,12). But in most cases the reaction is accompanied by side reactions and rearrangements of the N-oxide (13). More recently, we found that the two related dyes, resazurin and resorufin, in the presence of triethanolamine (TEOHA) produce radicals that are efficient photoinitiators of aqueous acrylamide polymerization (14).…”
Section: Introductionmentioning
confidence: 52%
“…The photoinduced deoxygenation of N-oxides has been reported previously for other molecules (10) and was found to proceed on irradiation of N-oxide alone or in the presence of suitable acceptors such as amines (11,12). But in most cases the reaction is accompanied by side reactions and rearrangements of the N-oxide (13). More recently, we found that the two related dyes, resazurin and resorufin, in the presence of triethanolamine (TEOHA) produce radicals that are efficient photoinitiators of aqueous acrylamide polymerization (14).…”
Section: Introductionmentioning
confidence: 52%
“…2) (El Sayed 2000). oxidation products that were papaverinol, papaveraldine, and papaverine N-oxide (106) under the influence of UV light, was reported (Girreser et al 2003;Souto-Bachiller et al 1999;Bremner and Wiriyachitra 1973). Papaverine hydrochloride, papaverinol, and papaveraldine chloroform solutions were exposed to UV light of 254 nm in atmospheric, aerobic and anaerobic (helium) condition, their photooxidation in chloroform solutions was studied (Piotrowska et al 2002;Muller and Dorfman 1934).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…56 The photolysis of papaverine N-oxide in polar solvents has been studied. 57 An X-ray crystallographic study of the solvation of O-tetraethyl-1,2-dehydronorlaudanosoline in ethanol, benzene and hydrochloric acid has been reported. 58 The trimethyl ether of imbricatine, derived from the star fish Dermasteria imbricata, 59 has been synthesised.…”
Section: Benzylisoquinolinesmentioning
confidence: 99%